Eddy Kinetic Energy and SST gradients global datasets and trends. Additionally, this dataset includes ocean basins and ocean processes masks. - Josué Martínez-Moreno; Andrew McC. Hogg; Matthew H. England; Navid C. Constantinou; Andrew E. Kiss; Adele K. Morrison (Zenodo, 2021)
This dataset includes the post-processed data used for the paper titled "Mesoscale kinetic energy response to changing oceans". The original data was obtained from AVISO+ SSH altimetryand NOAA optimal interpolated sea surface temperature (OISST): AVISO+ SSH:https://www.aviso.altimetry.fr/en/data/products/sea-surface-height-products/global/gridded-sea-level-heights-and-derived-variables.html NOAA-OISST:https://www.ncdc.noaa.gov/oisst From satellite observations of sea surface height (SSH) and sea surface temperature (SST) over the satellite record (1993 - 2019),EKE and SST gradients are derived. Then the fields are then temporally smoothed using a running average of 12 months. Trends and thesignificance of each field are finally computed with linear regression and a modified Mann–Kendall test (https://github.com/josuemtzmo/xarrayMannKendall). Geographical regions consist of the following ocean basins: the Southern Ocean, the Indian Ocean, thePacific Ocean, and the Atlantic ocean. These ocean basins were expert-defined to capture ocean processes at all scales (ocean_basins_and_dynamical_masks.nc). Dynamical regions (Fig. 5d): the Antarctic Circumpolar Current (ACC), the boundary currents and their extensions, the tropics, the subtropical ocean gyres, andthe remaining regions (ocean_basins_and_dynamical_masks.nc). Further information and scripts to reproduce the result of the manuscript can be found at:https://github.com/josuemtzmo/EKE_SST_trends Refer to https://github.com/josuemtzmo/xarrayMannKendall and https://github.com/josuemtzmo/EKE_SST_trends for more information and reproducibility of analysis. This dataset goes together with the paper titled "Mesoscale kinetic energy response to changing oceans"